Effect of Using Coolant on the Formation of Microcracks, Burr and Delamination in Bone Drilling Process - Rusnaldy Rusnaldy; Pratama Eka Putra Sijabat; Paryanto Paryanto; Toni Prahasto (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2021)
Direct approach for bone fracture treatment usually involves restoring the fractured parts to their initial position and immobilizing them with plates, screws and wires. This approach needs a bone surgery drilling to produce hole for screw insertion. But this drilling process causes mechanical damages, i.e microcracks, burr formation and delamination, that can reduce the stability of the fixation. One of the ways to minimize it is by using coolant. Moreover, it is noted that bone has anisotropic microstucture. The object of this study is to understand the effect of coolant on mechanical damages that occur in bone drilling and to understand the effect of microstructure difference on microcracks that occur in the drilled walls holes. Adult bovine bones and adult goat bones were used in this study as the specimens to represent differences in cortical bone microstructure. Five consecutive holes from the distal to the proximal in each specimen were generated using manual hand-drill (spindle speed (n) = 1000 rpm; drill bit (d) = 4 mm diameter) with the use of coolant as variation. The drilling holes then stained and observed using a microscope. As the result, it was found that the use of coolant can significantly reduce the drilling temperature. Microcracks, burr formation and delamination were found to be quite large in the drilling holes without coolant. However, there is no microcrack found in the drilling holes with coolant, there is only a small number of burr formation was found. In addition, it was found that the differences in bone microstructure affect the number and length of microcracks that occur in the wall of the hole. It can be concluded from this study that the application of coolant is very effective to reduce the drilling temperature and enhancing the quality of the hole generated by bone drilling and the higher the density of osteon in cortical bone, the easier the microcrack to initiate and propagate.